Creep and Stress Relaxation of Geogrids. Issue 5 (1st January 1997) - Leshchinsky, D.; Dechasakulsom, M.; Ling, H.I.; Kaliakin, V.N.
Abstract : Most research on the long term behavior of geosynthetics has focused on creep; very little data is available on the stress relaxation behavior of geogrids. Consideration of both creep and stress relaxation in design may ultimately produce a more efficient structure while allowing for the use of a smaller creep reduction factor. The results of an initial effort to experimentally identify the stress relaxation behavior of nine typical geogrids used to reinforce soil structures is presented. A simple test method that directly measures the stress relaxation of geogrids was developed. The geogrids were subject to initial loads of 40, 60, and 80% of their ultimate short term strengths. Each test was carried out for a period of one month, or until creep rupture occurred, whichever was shortest. The maximum potential stress relaxation was approximately 30% of the initial load for polyester geogrids, and 50% for polyethylene geogrids.